Pollution by hexachlorobenzene and pentachlorophenol in the coastal plain of São Paulo state, Brazil - Do Nascimento, N. R. [UNESP]; Nicola, S. M C; Rezende, M. O O; Oliveira, T. A. [UNESP]; Öberg, G. (Elsevier, 2004)
Organochlorine compounds were dumped by chemical industries during the 1970s in many areas of the coastal plain of São Paulo state in Brazil. These dumps, located on hillsides and in valleys, in both rural and urban environments, are responsible for soil and water pollution. The objective of this work was to determine how the pollutants have spread in an area occupied by a spodosol-type soil mantle. The study combines soil morphological observations with soil and water analysis of hexachlorobenzene (HCB) and pentachlorophenol (PCP) in soil toposequences. The results indicate that the highest pollutant concentrations are observed near the dump site and that the compounds contamination is increasing. A map integrating topography and chemical concentrations was created to visualize the spatial distribution of HCB levels in the landscape. Physical and chemical analyses were performed to measure HCB and PCP levels in the soil. Soil water appears to act as a vector of HCB, probably through complexation with and dispersal of dissolved organic matter. The persistence of HCB at the studied site is most likely due to the low pH values in combination with a high content of organic matter. HCB was consistently found in higher concentrations than PCP. It is plausible that the cause of this difference is that PCP is degraded more easily under sunlight than HCB and that degradation of PCP under acid conditions leads to the formation of HCB. © 2003 Published by Elsevier B.V.
Keywords: Aquifer pollution; Hexachlorobenzene; Organochlorine pesticide; Pentachlorophenol; Soil pollution; Spodosol; Chlorine; Degradation; Morphology; Phenols; Water analysis; Water pollution; Organochlorine compounds; Soils; aquifer pollution; coastal plain; hexachlorobenzene; PCP; soil pollution; Brazil; Sao Paulo [Brazil]; South America